Jellyfish swarms and degree of exposure and vulnerabil-ity of recreational and tourist activities on beaches. Methodological approach to their assessment in the Lagos-Ferrara sector (Málaga, Spain) - Cantarero-Prados, Francisco José; Moreno Portillo, Alejandro Miguel (My University, 2020)
An important part of the economy of the municipalities on the southern Spanish coast revolves around tourist activity, whose main attraction is the sun and beach. Events such as the arrival of swarms of jellyfish on their beaches have generated a certain amount of fear in the tourism sector. This work presents a methodological essay to evaluate the possible impact of this phenomenon on the use of the beach and the tourist economic activity linked to it. The chosen study area is the stretch of coast between the beach-es of "Lagos" and "Ferrara" (eastern coast of the province of Málaga). It is developed from a risk management perspective, addressing exposure and vulnerability factors. The sources are mainly surveys. The results show that in the short term there are no clear consequences, but there are in the long term.
Keywords: Mares y océanos; Costas - España - Málaga (Provincia); Medusas - Control integrado; Vulnerability, beaches, jellyfish, risk, tourism, Málaga,; Vulnerability; Beaches; Jellyfish; Risk; Tourism; Málaga; Costa - España - Málaga (Provincia)